Governance Reporting in Humanitarian Philanthropic Organizations - Md Ali, Nur Solehah Aqilah; Ramli, Nathasa Mazna (‘Abqari Journal, 2020)
This study emphasized on governance reporting of Malaysian humanitarian philanthropic organizations. The organization’ responsibilities are to report adequate and comprehensive information on the main activities and revenues to their stakeholders. Therefore, an organization should abide to mandatory reporting and may also voluntarily report other information to enhance the understanding of stakeholder toward the activities. This study observes five selected humanitarian philanthropic organizations are listed on Companies Commission of Malaysia (CCM) which the organizations formed for the non-profit activities. The non-profit organization also known as company limited by guarantee (CLBG). Each company’s latest annual report and website had been analyzed using content analysis and evaluation of the level of disclosure by using binomial logic. As a result, this study identifies the governance reporting and disclosure practices by the companies. Comparison between governance reporting in the annual report and website are also made for each of the company. The findings of this study will suggest the need for philanthropic organizations in Malaysia to enhance its governance reporting especially in their annual report. This study provides evidence on governance reporting and complements prior research. The results of the research indicate that maintaining and strengthening governance reporting practices in humanitarian philanthropic organization in Malaysia to the accountability system.